Les conversations paysagères 2004. Métiers du paysage Textes du colloque du 13 octobre 2004, Espace Senghor - Gembloux (Belgique) - Neirinck, P.; Toussaint, A.; Feltz, C.; Roggemans, J. (Uliège Library, 2006)
In September 2004, the first class of the Bachelor of Landscape Architecture of the Bachelor of Landscape Architecture, a 5-year university course in 5 years, co-organized by three institutions of the French of the French Community of Belgium, the University Faculty of the University Faculty of Agronomic Sciences of Gembloux, the Haute École Charlemagne (I.S.I. Gembloux and Huy) and the ʼInstitut Supérieur d ʼArchitecture La Cambre Brussels. Lʼenseignement de l ʼarchitecture du paysage en French-speaking Belgium is however not new, it has a long tradition. even already has a long tradition. And the ancient training of the Gembloux graduate school is recognized, mainly l ʼétranger mais reste insuf fisamment connue en Belgium. It is in this context that a one-day seminar was organized on October 13, 2004. 2004, a study day entitled "Conversations Conversations on Landscape 2004", the first biennial meeting of the landscape. This dialogue, a meeting between the disciplines and professions of the landscape has a double objective. On the one hand, it intends to make known the work and the of landscape architecture in French-speaking Belgium, as well as the genesis and as well as the genesis and the institutions of lʼenseignement en cette matière. This is the subject of the premier part of the study day. On the other hand, according to the European Landscape Convention of Florence 2000 to which the Walloon Region has adhered since the Walloon Region joined in December 2001, landscape management of landscapes requires us to move beyond the scale of parks and parks and gardens to consider the whole range of objectives of the of the Convention, namely, to manage, protect and develop landscapes. ger landscapes. It is therefore now necessary for the landscape disciplines to converse, to know each other and to recognize each other. In this perspective, the second and the second and major part of the interventions opens the debate between the disciplines and professions of landscape, with presentation of exemplary cases stimulating the common reflection. This issue of the "Colloquia" series publishes the papers presented at the 2004 Landscape Conversations day.